Fuzzy Observer-Based Control of Servomechanisms Subject to Friction Dynamics - Mostefai, L.; Denai, M.; Hori, Y. (IECON 2007 - 33rd Annual Conference of the IEEE Industrial Electronics Society, 2007)
This paper proposes an approach of dynamic fuzzy modeling applied to friction compensation to enhance the performance of a servodrive system in tracking a trajectory. The fuzzy observer is derived from the dynamic nature of friction, and is used to suppress friction-induced errors. The linearity of the local models simplifies the design of the observer and its estimation capabilities are improved with the addition of a nonlinear compensating gain. Simulation results demonstrate the effectiveness of this observer-based control strategy.